Filamentary Electron-beam Heating in Solar Flares - Michalina Litwicka; Petr Heinzel; Jana Kašparová (The Astrophysical Journal)
Radiation-hydrodynamic simulations of the solar-flare chromospheric emission very often lead to an excess of the line intensities when compared to observations. Various studies suggest that the flare loops have a certain intrinsic, multithread internal structure, which is still not resolved by current telescopes. Taking this into account, we want to test and compare two different approaches for flare simulations. The first approach is the commonly used one, based on a continuous flux of nonthermal electrons heating the chromosphere for a rather long time. In the second approach, we consider the heating by short beam pulses consecutively within spatially unresolved filaments. Superposition of these short-duration pulses gives us the same electron-beam flux as in the first approach, but we are showing that the filamentary heating generates lower intensities in both the H α and Mg ii k lines, as expected.